Prokaryotic diversity of the rhizosphere from Argentinean wine-producing regions - Andres Martin Toscani; Monica Oyuela Aguilar; Constanza Rey; Ramiro Eugenio Rocco Welsh; Alex Gobbi; Maria Florencia del Papa; Liliana Carmen Semorile; Lars Hestbjerg Hansen; Mariano Pistorio (OENO One)
Argentina stands as the seventh-largest wine producer. Its broad geographical and climatic diversity contributes to the production of wines with distinctive regional characteristics. Microorganisms associated with vines play a crucial role in wine quality. Recent studies have revealed significant differences in microbial communities between grape varieties and vineyard locations. In this work, we conducted a comprehensive examination of the diversity of prokaryotic microorganisms in the rhizosphere of vineyards located in three wine regions of Argentina. We used next-generation sequencing methods, concentrating the analysis on two relevant cultivars, Malbec and Cabernet Sauvignon. Both varietals have attracted significant interest in recent research given their distinctive characteristics, which vary according to the geographic growing region. The soil physicochemical properties of the vineyards analysed, were evaluated by principal component analysis, and clustering analysis, allowing us to identify differences among them. Despite no significant variations were observed between Malbec and Cabernet-Sauvignon vineyards, significant differences in microbial diversity were observed among the analysed locations. Taxonomic identification showed distinct microbial compositions across regions, with notable differences in abundance at the family level. Canonical correspondence analysis indicated correlations between soil physicochemical properties and microbial families, highlighting the influence of soil characteristics on microbiota composition. These differences in microbial populations set a site-specific prokaryotic profile that could be used as an identifying signature. Comprehending these interactions is essential for improving vineyard management techniques, ultimately shaping the sensory characteristics of wines crafted in diverse regions.